Literature Review: The Relationship Between Dietary Patterns, Physical Activity, And Medication Compliance With The Increase In Blood Sugar Levels In Diabetes Mellitus Patients - Rahayu Rahayu; Hana Putri Pratiwi; Rifky Adhitya Abdillah; Ni Wayan Wiwin Asthiningsih (International Journal of Health Engineering and Technology, 2026)
Diabetes mellitus is a chronic metabolic disorder characterized by hyperglycemia due to impaired insulin secretion or action. Blood glucose control in patients with type 2 diabetes mellitus is influenced by various factors, including dietary patterns, physical activity, medication adherence, as well as psychosocial factors such as stress and family support. This study used a literature review method by searching scientific articles through Google Scholar, PubMed, and ScienceDirect within the publication period of 2022–2026. Selected articles focused on the relationship between diet, physical activity, and medication adherence with blood glucose levels in patients with type 2 diabetes mellitus. The review findings indicate that most studies show a significant relationship between dietary patterns, physical activity, and medication adherence with blood glucose levels. Physical activity and dietary adherence contribute to better glycemic control, while medication adherence shows inconsistent results. Other factors such as family support, stress levels, and smoking habits also influence blood glucose stability. Blood glucose control in diabetes mellitus is multifactorial. Proper diet and regular physical activity improve insulin sensitivity and glucose metabolism. Medication adherence is important, but not always directly associated with glycemic control due to the influence of individual and lifestyle factors. Dietary patterns, physical activity, and medication adherence play important roles in controlling blood glucose levels in patients with type 2 diabetes mellitus, although results are not always consistent. Diabetes management requires a comprehensive approach including lifestyle modification and psychosocial support.